Causes and Self-regulatory Mechanisms of Frustration: A Qualitative Exploration of Rock Climbers - Chuyao, Fan; Yinqiu, Zhang; Jin, Wang; Yuannan, Zheng; Wallace, C. Norwood (Journal of Human Psychology, 2020)
In recent years, rock climbing has become increasingly popular around the world. However, due to its challenging and competitive nature, it is common for rock climbers to encounter frustration. It leads to negative emotions, reducing participation, and withdrawal behavior, which requires effective self-regulation. Therefore, the purpose of this study was to explore the causes and self-regulatory mechanisms of frustration in rock climbing. Using qualitative methods, 15 rock climbers were interviewed, and 6 themes were identified by thematic analysis. Task comparison and social comparison are the main causes of frustration in rock climbing. The self-regulatory mechanism of task comparative frustration includes focusing on tasks and habitual reflection. The self-regulatory mechanism of social comparative frustration involves emotion regulation and changing goal orientation. It is suggested that future rock climbers, especially beginners, deal with frustration through the self-regulatory mechanisms that can help them enjoy and pursue rock climbing.
Keywords: Frustration; causes; self-regulatory mechanisms; rock climbers; qualitative methods